2001
DOI: 10.1039/b105656p
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The presence of a phthalate in dry polymer membranes consisting of polyvinylpyrrolidone (PVP) and AgBF4, AgBF4-PVP, provides long-term stability and better performance for the separation of propylene/propane gas mixtures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 10 publications
1
37
0
Order By: Relevance
“…For example, the polymer electrolyte membranes consisting of AgBF 4 dissolved in POZ, PVP or PEO containing oxygen atom show the slightly continuous decrease in separation performance. 50,51 This is possibly due to the reduction of silver ions to silver nanoparticles during the separation process, because polymers such as PEO, POZ or PVP used as a polymer solvent in the solid polymer electrolytes also plays a role as a reducing agent for the silver salts. 22,[50][51][52][53] It has been recently reported that plasticizers such as dialkyl and diaryl phthalates are highly effective to prolong the carrier activity of the free silver ion, thereby increasing the performance of the dry polymer electrolyte membranes, as shown in Figure 13.…”
Section: Membrane Performancementioning
confidence: 99%
See 2 more Smart Citations
“…For example, the polymer electrolyte membranes consisting of AgBF 4 dissolved in POZ, PVP or PEO containing oxygen atom show the slightly continuous decrease in separation performance. 50,51 This is possibly due to the reduction of silver ions to silver nanoparticles during the separation process, because polymers such as PEO, POZ or PVP used as a polymer solvent in the solid polymer electrolytes also plays a role as a reducing agent for the silver salts. 22,[50][51][52][53] It has been recently reported that plasticizers such as dialkyl and diaryl phthalates are highly effective to prolong the carrier activity of the free silver ion, thereby increasing the performance of the dry polymer electrolyte membranes, as shown in Figure 13.…”
Section: Membrane Performancementioning
confidence: 99%
“…50,51 This is possibly due to the reduction of silver ions to silver nanoparticles during the separation process, because polymers such as PEO, POZ or PVP used as a polymer solvent in the solid polymer electrolytes also plays a role as a reducing agent for the silver salts. 22,[50][51][52][53] It has been recently reported that plasticizers such as dialkyl and diaryl phthalates are highly effective to prolong the carrier activity of the free silver ion, thereby increasing the performance of the dry polymer electrolyte membranes, as shown in Figure 13. 50,51 Stability enhancement is attributed to the fact that the silver ions are more strongly held by the phthalate groups to form chelating bonds and consequently their reduction reaction to metal is mostly prevented.…”
Section: Membrane Performancementioning
confidence: 99%
See 1 more Smart Citation
“…The interaction of olefins with silver ions confined to a carbonyl-containing polymer electrolyte membrane has been demonstrated clearly by FTIR spectroscopy, [3,4] but the interaction of olefins with silver ions bound to sulfonate groups has never been investigated. For this reason, we conducted a FTIR spectroscopic investigation of the interaction of sulfonate-bound silver ions with propylene using 2 b.…”
Section: Resultsmentioning
confidence: 99%
“…The complex membranes of silver ion with the oxygen atoms of amide groups commonly showed a poor long-term stability. 19,20 In this paper, the coordinative interaction of silver ions with C=C of PHMV and their ionic interactions with counteranions are elaborated in detail. More specifically, the dissociation and π-complexation behavior in PHMV complexes with three silver salts, i.e., AgBF 4 , AgClO 4 and AgCF 3 SO 3 are investigated, and ionic constituents such as free ions, ion pairs and higher order ionic aggregates are additionally characterized.…”
Section: Introductionmentioning
confidence: 99%